2017
DOI: 10.1007/s10803-017-3207-0
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: The Negev Hospital-University-Based (HUB) Autism Database

Abstract: Elucidating the heterogeneous etiologies of autism will require investment in comprehensive longitudinal data acquisition from large community based cohorts. With this in mind, we have established a hospital-university-based (HUB) database of autism which incorporates prospective and retrospective data from a large and ethnically diverse population. The collected data includes social-demographic characteristics, standardized behavioral testing, detailed clinical history from electronic patient records, genetic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 62 publications
0
38
0
Order By: Relevance
“…There was no significant difference in the age of participating children across groups ( t (129)) = 0.64, p = 0.57, two-tailed t test). Children with autism were recruited through the Negev Autism Center [ 33 ]. Control children of the same age were recruited from the community through an online forum at Ben Gurion University.…”
Section: Methodsmentioning
confidence: 99%
“…There was no significant difference in the age of participating children across groups ( t (129)) = 0.64, p = 0.57, two-tailed t test). Children with autism were recruited through the Negev Autism Center [ 33 ]. Control children of the same age were recruited from the community through an online forum at Ben Gurion University.…”
Section: Methodsmentioning
confidence: 99%
“…Our final analyzed sample included 111 children who were recruited at the National Autism Research Center of Israel [Meiri et al, 2017]. This sample consisted of 71 children diagnosed with ASD according to DSM-5 criteria (mean age: 5.1 years old AE 1.8, 59 males), and 40 typically developing children (mean age: 4.5 years old AE 2.1, 25 males).…”
Section: Participantsmentioning
confidence: 99%
“…Seventy studies were found on social, educational, and psychological research including Arabic individuals with ASD and their family members in the following Arab countries: Saudi Arabia, Kuwait, Bahrain, Jordan, Lebanon, UAE, Oman, Egypt, Qatar, Libya, Iraq, West Bank, Syria, Tunisia. A small number of studies (n = 12, 17%) were conducted in non-Arab countries but with Arab populations (Baker 2017;Barnevik-Olsson et al 2008;Dolev et al 2016;Esler et al 2017;Estrem and Zhang 2010;Fox et al 2017;Kediye et al 2009;Meiri et al 2017;Perepa 2014;Raz et al 2015;Sher-Censor et al 2017; Walker-Dalhouse and Dalhouse 2015). None of the 70 studies identified were published in Arabic.…”
Section: Resultsmentioning
confidence: 99%
“…There were few studies that explored the social and communication behaviour of Arab individuals with ASD (n = 10, 14%) (Table 3 and Online Resource S3). Of those 10, three studies were conducted in non-Arab countries but with Arab populations (Meiri et al 2017;Perepa 2014; Walker-Dalhouse and Dalhouse 2015). The total number of Arab participants included in these studies was 44.…”
Section: Social and Communication Behaviour Of Arab Individuals With Asdmentioning
confidence: 99%